The image of war in Simone de Boer’s novel The Blood of Others - Abed, Faten Mohammed (Zanco Journal of Human Sciences, 2021)
The topic of war is the most controversial topic in all literary arts, especially the novel, because it deals with the event that directly affects human life and his fate. This study deals with the subject of World War II in which many countries of the world participated in, leading to the killing of millions of civilians without any justification, leaving negative effects on the lives of the remaining living among them. from here launched this study, titled “The Image of War in the novel The Blood of Others” by the French writer Simone de Beauvoir, where she harnessed her literary and philosophical creativity as a writer and philosopher to address the issue of war and the negative effects it leaves on human life, specifically the events that took place in the World War II The second one, which began on the 1st of September 1939 and ended on the 2nd of September 1945, in which 3o nations of the world were involved in. This study consists of four sections. The first section deals with the subject of the revolution as a reaction by French youth against the war massacres, the second section addresses the phenomenon of (Absurdity) and its birth as a new phenomenon resulting from the human feeling of loss and fear during the war, The third study deals with the existential phenomenon linked The freedom of mankind, where man always tries to prove his existence and his struggle for survival, while the fourth and final section deals with the issue of the (lost war) through the fall of Paris in the hands of German soldiers led by Hitler, and making great sacrifices by the French without justification